2022
DOI: 10.1007/s12144-022-03704-9
|View full text |Cite
|
Sign up to set email alerts
|

Rational emotive intervention for work-family conflict and female primary school teachers’ well-being

Abstract: Globally, work and family conflict has been investigated by many researchers. Yet there is an increased prevalence of work-family conflict and its influence on the well-being of the female teaching population, especially Nigerian primary school teachers. This incidence has kept a good proportion of schoolteachers vulnerable to health problems as well as affected their wellbeing. This study evaluates the effect of rational emotive behaviour therapy on improving the well-being of female teachers with irrational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 42 publications
2
24
0
1
Order By: Relevance
“…Organizational atmosphere significantly affects burnout as well as work-family conflict, which is obvious. Additionally, several research speculated that work-family conflict might mediate the connections between work demands and intentions to leave their jobs (Li et al, 2022), job satisfaction (Giancaspro et al, 2022), and happiness (Ifelunni et al, 2022). The current study discovered a positive correlation between work-family conflict and teacher burnout, which was in line with other research (MA et al, 2014).…”
Section: Burnout As a Mediator Between Work-family Conflict And Job S...supporting
confidence: 90%
“…Organizational atmosphere significantly affects burnout as well as work-family conflict, which is obvious. Additionally, several research speculated that work-family conflict might mediate the connections between work demands and intentions to leave their jobs (Li et al, 2022), job satisfaction (Giancaspro et al, 2022), and happiness (Ifelunni et al, 2022). The current study discovered a positive correlation between work-family conflict and teacher burnout, which was in line with other research (MA et al, 2014).…”
Section: Burnout As a Mediator Between Work-family Conflict And Job S...supporting
confidence: 90%
“…[29] REBT studies have argued that well application of REBT techniques and its principles could help to decrease depressive symptoms. [25,27,30] With these in mind, we investigated the impacts of REBT in treating depressogenic beliefs associated with schoolchildren with atypical behaviors in Abia state, Nigeria. This study was guided by some hypotheses.…”
Section: Introductionmentioning
confidence: 99%
“…[26] The researcher further remarked that the REBT model proposes that individuals' cognitive, emotional, and behavioral consequences are solely determined by the belief system (B). [27] The belief system that produces negative consequences is due to irrational assumptions. Rational belief is the logical, flexible, and non-extreme way of representing realities while irrational ones are characterized by extreme, rigid, and illogical.…”
Section: Introductionmentioning
confidence: 99%
“…Since the study outcome revealed the long-term effects of CBT, cognitive behavioral therapists, psychologists, school counselors, teachers in colleges, and other schools should adopt the principles of CBT in helping students with behavioral problems. 76 - 79 By practicing the assumptions of CBT, inappropriate behaviors such as pathological behaviors and the types in which students excessively indulge in could be reduced using CBT.…”
Section: Discussionmentioning
confidence: 99%